2021
DOI: 10.1111/cge.13911
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentation and molecular characterization of a novel patient with variant POC1Arelated syndrome

Abstract: Biallelic pathogenic variants in POC1A result in SOFT (Short‐stature, Onychodysplasia, Facial‐dysmorphism, and hypoTrichosis) and variant POC1A‐related (vPOC1A) syndromes. The latter, nowadays described in only two unrelated subjects, is associated with a restricted spectrum of variants falling in exon 10, which is naturally skipped in a specific POC1A mRNA. The synthesis of an amount of a POC1A isoform from this transcript in individuals with vPOC1A syndrome has been believed as the likely explanation for suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…Giorgio E et al suggested that the POC1A gene was a gene with pleiotropic effects, and variants affecting exon 10 only could cause variant POC1A-related (vPOC1A) syndrome instead of typical SOFT syndrome, whose main clinical features included an extreme dyslipidemia with insulin resistance and acanthosis nigricans, because variants restricted to exon 10 of the POC1A gene affected only two of the three mRNA isoforms, leaving a functional isoform [ 7 ]. To date, three vPOC1A syndrome individuals had been reported [ 4 , 7 , 12 ]. The splicing variant detected in our patient has been proven to cause exon 9 skipping which are necessary in all isoforms and affect WD40 domain integrity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Giorgio E et al suggested that the POC1A gene was a gene with pleiotropic effects, and variants affecting exon 10 only could cause variant POC1A-related (vPOC1A) syndrome instead of typical SOFT syndrome, whose main clinical features included an extreme dyslipidemia with insulin resistance and acanthosis nigricans, because variants restricted to exon 10 of the POC1A gene affected only two of the three mRNA isoforms, leaving a functional isoform [ 7 ]. To date, three vPOC1A syndrome individuals had been reported [ 4 , 7 , 12 ]. The splicing variant detected in our patient has been proven to cause exon 9 skipping which are necessary in all isoforms and affect WD40 domain integrity.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, SOFT syndrome could be classified as a type of ciliopathy. To our best knowledge, only 13 variants of POC1A gene have been reported until now, including 7 missense mutations, 2 nonsense mutations and 4 frameshift mutations [1][2][3][4][5][6][7][8][9][10][11][12] (Fig. 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since these initial reports ( 1 , 2 , 3 ), 12 additional affected kindreds have been described ( 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ). In addition to the cardinal syndromic features, three of 31 patients reported to date also manifested severe dyslipidaemic insulin resistance (IR) ( 7 , 11 , 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…As an important component of the centrosome, POC1A (POC1 centriolar protein homolog A), which is also called WDR51A, plays an important role in the formation and steady state of centrioles in biological processes (Keller et al,2009). Numerous studies have con rmed that POC1A is related with facial dysmorphism and hypotrichosis (SOFT) syndrome, onychodysplasia, short stature, which is associated to abnormalities in cell mitosis (Koparir et al,2015,Majore et al,2021. All these studies reveal that POC1A may play a important role in cell proliferation.…”
Section: Introductionmentioning
confidence: 99%